2002
DOI: 10.1113/jphysiol.2002.022343
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Dependent Synapse Withdrawal at Axotomised Neuromuscular Junctions in Wlds Mutant and Ube4b/Nmnat Transgenic Mice

Abstract: Axons in WldS mutant mice are protected from Wallerian degeneration by overexpression of a chimeric Ube4b/Nmnat (Wld) gene. Expression of Wld protein was independent of age in these mice. However we identified two distinct neuromuscular synaptic responses to axotomy. In young adult Wlds mice, axotomy induced progressive, asynchronous synapse withdrawal from motor endplates, strongly resembling neonatal synapse elimination. Thus, five days after axotomy, 50–90 % of endplates were still partially or fully occupi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
157
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 84 publications
(178 citation statements)
references
References 58 publications
(80 reference statements)
21
157
0
Order By: Relevance
“…92 Another study showed that in Wlds mice over seven months of age, axotomy-induced synapse withdrawal from motor endplates is no longer protected, and reverts to a wild-type pattern. 93,94 These findings indicate that the molecular pathways involved in the NAD + /Wlds mediated neural protection might be regulated by age-related changes. The age factor is probably working downstream of the Wlds gene.…”
Section: Age Nad and Neural Protectionmentioning
confidence: 94%
“…92 Another study showed that in Wlds mice over seven months of age, axotomy-induced synapse withdrawal from motor endplates is no longer protected, and reverts to a wild-type pattern. 93,94 These findings indicate that the molecular pathways involved in the NAD + /Wlds mediated neural protection might be regulated by age-related changes. The age factor is probably working downstream of the Wlds gene.…”
Section: Age Nad and Neural Protectionmentioning
confidence: 94%
“…The weaker Wld S protection at NMJs, compared to the axonal trunk (Gillingwater et al, 2002), could be explained by the longer distance that Wld S needs to travel to reach the nerve endings and by dilution into the extensive terminal axonal branches. The age dependence of synapse withdrawal could be due to progressive decrement of axonal transport efficiency correlating with aging.…”
Section: Discussionmentioning
confidence: 99%
“…Because Wld S protective efficacy is dose dependent (Mack et al, 2001), axon protection would not be expected at such low levels, but low doses of axonally targeted NMNAT1 delay Wallerian degeneration for even 5 weeks. Moreover, neither a heterozygous dose of Wld S protein in young mice nor a homozygous dose in older mice is sufficient to delay NMJ dener- vation (Gillingwater et al, 2002;Wong et al, 2009), whereas these very low doses of axonally targeted NMNAT1 preserve axotomized NMJs for 6 d and retain this ability even in older mice. Even though Ax-NMNAT1 has substantially higher potency than Wld S , important similarities indicate that its mechanism of protection is the same as the Wld S mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-apoptotic interventions do not prevent axonal degeneration [59]. Dendrites and synapses also seem to contain compartmentalized selfdegenerative programmes, which may be important in synaptic plasticity as well as in ageing and neurodegeneration [60]. Some of these do appear to be related to apoptosis [57].…”
Section: Calcium Dysregulationmentioning
confidence: 99%